Surgical Treatment and Complications of Pectus Excavatum in Childhood, Adolescence and Adulthood: A Literature Review on the Nuss Technique - Alicija Šavareikaitė; Paulius Valatka (Lietuvos Chirurgija)
Background / Objective. The Nuss procedure effectively addresses Pectus Excavatum through minimally invasive, semi-permanent insertion of metal bars, aiming to diminish the deformity and reshape the growing thorax contour. This study aims to analyze and summarize large-scale healthcare data on characteristics of complications in patients undergoing surgical correction for chest deformities, treated with the Nuss technique. Methods. A systematic review of scientific literature was performed utilizing PubMed, with the selection criteria focused on publications detailing the diagnosis and surgical treatment of Pectus Excavatum. The systematic review adhered to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for systematic reviews. Results. According to established criteria, 404 publications were identified, of which 100 were deemed suitable to proceed with further analysis of the entire text. For the final analysis, we selected 27 articles. The patient sample size was 2,401. The average age of patients was 14.54 (ranging from 18 months to 51 years). Of all patients, distribution by gender was as follows: 511 females and 1,890 males. A total of 61 categories of complications were identified, totalling 850 complications. Intraoperative complications accounted for 1.29%, while postoperative complications accounted for 98.71%. The most common complications were pneumothorax (29.91%), displacement of the steel bar (11.32%), and pleural effusion (9.65%). Only 6 articles provided data on chest drainage, which was required for a total of 398 patients. The average hospitalization duration across all articles is approximately 7.5 days. Conclusions. While the Nuss technique effectively corrects deformities in Pectus Excavatum, postoperative complications like pneumothorax and steel bar displacement remain common. This underscores the need for meticulous patient selection and postoperative care to enhance safety and improve surgical outcomes.